Differential Spermatozoal Protein Expression Profiles in Men With Varicocele Compared to Control Subjects: Upregulation of Heat Shock Proteins 70 and 90 in Varicocele - Chan, Chying-Chyuan; Sun, Guang-Huan; Shui, Hao-Ai; Wu, Gwo-Jang (Urology (Ridgewood, N.J.), 2013)
To identify candidate proteins with potential roles in varicocele. This case-control study recruited 20 patients with varicocele (grade II) and 20 age-matched healthy control subjects. Two-dimensional gel electrophoreses (2-DE) and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) were used to screen for and identify differentially expressed proteins in sperm samples from the 40 study subjects. A total of 15 proteins were repeatedly detected with significant differences in percent spot volume (P <.05) and were identified as proteins of interest. Of these, 4 showed significantly lower expression in the varicocele group compared to the control group, and 11 showed significantly higher expression in the varicocele group, including heat shock proteins (HSPs) 70 and 90. Significant upregulation of HSP 70 and HSP 90 in subjects with varicocele was further validated by Western blot and immunocytochemistry. These results suggest that increased expression of HSP 70 and HSP 90 may be associated with infertility in varicocele. Delineation of a potential subset of heat-related proteins specifically regulated in the context of varicocele may allow for the detailed elucidation of the mechanism underlying infertility in this condition.